Aircraft landing gear design : principles and practices - Currey, Norman S. (American Institute of Aeronautics and Astronautics, 1988)
This is the only book available today that covers military and commercial aircraft landing gear design. It is a comprehensive text that will lead students and engineers from the initial concepts of landing gear design through final detail design. The book provides a vital link in landing gear design technology from historical practices to modern design trends, and it considers the necessary airfield interface with landing gear design. The text is backed up by calculations, specifications, references, working examples.
Keywords: Airplanes -- Landing gear -- Design and construction.; elektronické knihy; electronic books